The Influence of Digital Financial Literacy and Financial Technology Use on MSME Financial Performance with Financial Inclusion as a Mediating Variable among MSMEs in Sidoarjo - Silfiyah Wahdah; Nur Rokhmad Nuzil (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The expansion of digital finance creates opportunities for micro, small, and medium enterprises (MSMEs) to improve their financial performance while simultaneously requiring adequate digital financial capabilities and access to appropriate financial services. This study examines the effects of digital financial literacy and financial technology use on MSME financial performance, with financial inclusion as a mediating variable, in Sidoarjo Regency. A quantitative approach with an explanatory research design was employed. The study involved 116 MSME respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed through path analysis and the Sobel test to assess direct and indirect effects. The findings support the examination of digital financial literacy, financial technology use, financial inclusion, and financial performance as an integrated framework for understanding MSME digitalization. The study concludes that strengthening digital financial capabilities and expanding access to financial services are important for supporting MSME financial performance. By integrating technological capability, financial access, and business outcomes within a single analytical framework, this study contributes to understanding the role of financial inclusion in MSME digitalization. The findings underscore the need for MSME owners and policymakers to coordinate financial literacy development, financial technology adoption, and financial inclusion initiatives.